Synthesis and Modification of Polyaniline Nanostructure by Using Various Surfactants - Soleimani Lashkenari, M.; Davodi, B.; Eisazadeh, H. (Asian Journal of Chemistry, 2010)
In this study, polyaniline nanocomposites were prepared in the aqueous media by using ammonium peroxy disulfate as an oxidant in the presence of various surfactants such as sodium dodecylbenzenesulfonate, poly(vinyl pyrrolidone) and hydroxypropylcellulose. Morphology, conductivity and chemical structure of the product were characterized by using scanning electron micrograph, four point probe method and fourier transform infrared spectrometer respectively. The results indicate that the morphology, yield, particle size and conductivity of products are dependent on the type of surfactant. The results also show that the intensity of peaks is dependent on the type of surfactant.